Low dose decitabine in very high risk relapsed or refractory acute myeloid leukaemia in children and young adults. (23rd February 2013) - Phillips, Christine L.; Davies, Stella M.; McMasters, Richard; Absalon, Michael; O'Brien, Maureen; Mo, Jun; Broun, Randall; Moscow, Jeffrey A.; Smolarek, Teresa; Garzon, Ramiro; Blum, William; Schwind, Sebastian; et al.
Summary Low‐dose decitabine has encouraging activity and tolerability in adults with acute myeloid leukaemia (AML), but paediatric experience is lacking. We report our retrospective experience with decitabine in eight children and young adults (median age 4 years) with refractory/relapsed AML, who had failed multiple regimens or were not candidates for standard retrieval regimens due to prior toxicities. Three of eight patients (38%) had complete response (CR; 1 each of CR, CR with incomplete platelet recovery and CR with incomplete count recovery). Best responses were observed after a median of 2·5 cycles (range 1–4 cycles). Four patients received subsequent allogeneic stem cell transplant, and two remain in long‐term CR.